18F-Fluorodeoxyglucose-Positron Emission Tomography Imaging Detects Response to Therapeutic Intervention and Plaque Vulnerability in a Murine Model of Advanced Atherosclerotic Disease—Brief Report. Issue 12 (December 2020) - Jarr, Kai-Uwe; Ye, Jianqin; Kojima, Yoko; Nanda, Vivek; Flores, Alyssa M.; Tsantilas, Pavlos; Wang, Ying; Hosseini-Nassab, Niloufar; Eberhard, Anne V.; Lotfi, Mozhgan; Käller, Max; Smith, Bryan R.; et al.
Abstract : Objective: This study sought to determine whether 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography could be applied to a murine model of advanced atherosclerotic plaque vulnerability to detect response to therapeutic intervention and changes in lesion stability. Approach and Results: To analyze plaques susceptible to rupture, we fed ApoE −/− mice a high-fat diet and induced vulnerable lesions by cast placement over the carotid artery. After 9 weeks of treatment with orthogonal therapeutic agents (including lipid-lowering and proefferocytic therapies), we assessed vascular inflammation and several features of plaque vulnerability by 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography and histopathology, respectively. We observed that 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography had the capacity to resolve histopathologically proven changes in plaque stability after treatment. Moreover, mean target-to-background ratios correlated with multiple characteristics of lesion instability, including the corrected vulnerability index. Conclusions: These results suggest that the application of noninvasive 18 F-fluorodeoxyglucose-positron emission tomography/computed tomography to a murine model can allow for the identification of vulnerable atherosclerotic plaques and their response to therapeutic intervention. This approach may prove useful as a drug discovery and prioritization method. Abstract : Supplemental Digital Content is available in the text.